Preventive Activities the Teacher to Prevent Adolescent Aggression - Yordanka Dimitrova; Marinela Grudeva (ARPHA Proceedings, 2019)
The problem of aggressiveness of adolescents is one of the central socio-pedagogical problems that affects society at large, causes deep concern among teachers, parents, and causes an acute scientific and practical interest of foreign and native researchers. In connection with the spread of aggression in the adolescent environment, there is a need to consider its prevention and correction in school. Diagnostic research and prevention of adolescent aggression at school is an integral component of the activity of classroom teacher. The article deals with the essence of aggressiveness, especially aggressive behavior of teenagers at school, discusses the factors that influence the expression of aggression, specifically the destruction of the traditional models of education. It also points to the need to apply effective methods and techniques for preventing and correcting the aggressive behavior of adolescents in school by means of classroom teacher’s activities. The material may be useful for classroom teachers, specialists of psychological services accompanying educational institutions.